A Meta-analysis on Vitamin D Deficiency in Patients with Sickle Cell Disease - Sagad Omer Obeid Mohamed; Fatima Abdelhakam Abdellatif Mohamed Elmugadam; Hiba Faroug Mohamed Awadalla; Abdalla Omer Obeid Mohamedali; Mansour Osman Alhaj Alawad; Ahmed Abdulgadir Noureddin; Afnan Abugundul Ahmed Osman; Esraa Mohamed Osman Mohamed; Gehad Abdelmonem Abdalla Ibrahim; Malaz Ahmed Osman Elsayed (Dr. Sulaiman Al Habib Medical Journal)
Vitamin D Deficiency (VDD) is reported to be more frequent with serious clinical outcomes in patients with Sickle Cell Disease (SCD). There is a wide disparity in data in the existing literature regarding the prevalence and risk of VDD in patients with SCD. These data require further summary and analyses for better accuracy. This review aimed to assess the association between VDD and SCD, and was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Medline/ PubMed, World Health Organization Virtual Health Library, ScienceDirect, and Google Scholar were used for the systematic search. A random effects model was used to estimate the pooled prevalence, Risk Ratio (RR), and Standardized Mean Difference (SMD) estimates with the corresponding 95% Confidence Interval (CI) using OpenMeta Analyst software version 10.10 (Tufts Medical Center, Boston, MA, USA). Twenty-five studies fulfilled the eligibility criteria. The prevalence of VDD among patients with SCD was 63.8% (95% CI, 52.5–75.1). The risk of VDD among patients with SCD was more than two times that of the general population (RR = 2.129; 95% CI, 1.024–4.423; p< 0.001). Serum vitamin D levels were significantly lower in SCD patients than in their controls (SMD = –1.883: 95% CI, –3.006 to -0.760; p< 0.001). This review provides a comprehensive view of the association between vitamin D status and SCD.